Inversión en Investigación, Desarrollo, Maquinaria y Equipo: Desempeño de la Industria Panificadora - Vélez Osorio, Iris María (2020)
Investment in research and development activities, machinery, equipment that allow the construction of innovation processes in the bakery sector have shown to significantly improve corporate performance. In this research these investments are analyzed in 68 organizations of the bakery sector, Recognizing the positive impact for the bakery sector of both investments, especially in an industry with significant barriers to innovation and a traditional production system. The results show the need for the smallest organizations in the sector, to greater investment in research and development, and the early creation of an innovation policy for the bakery sector.